Clinical Presentation and Histopathological Patterns of Renal Cell Carcinoma in Gezira Hospital for Renal Diseases and Surgery - Mohammed, Salih Yahia; Mansour, Mustafa Omran; Mohammed Ahmed, Mohammed Elemam (مجلة الجزيرة للعلوم الصحية; مجلد 9 عدد 2 (2013), 2013)
Background: Renal cell carcinoma (RCC) is the most common primary tumour of the kidney in adults, responsible for (80-85%) of renal tumours (1) . Due to the absence of studies in Sudan in assessing the pattern and presentation of RCC, we conducted this retrospective study in Gezira Hospital for Renal Diseases and Surgery, in the period from January 2006 to January 2012.  Objective: To determine the clinical presentation, pathological pattern and stages of RCC in patients who were treated in (GHRS) in the period of this study. Results: A total of 60 patients were diagnosed as RCC in the period of six years. The disease was more common in males, with a peak incidence in the fifth and sixth decades. The classical triad were observed in 19 patients .Mean duration of symptoms was 4 months. Some patients had metastasis in the lung, bones or liver at diagnosis. Most of the patients presented with haematuria (66.6%), a small number with cervical lymphadenopathy (6.7%), lower limb edema (3.3%) and non reducible varicocele (5%). conclusion: A large number of patients presented with a palpable loin mass, in contrast incidentally diagnosed cases were few .The age of presentation is one decade earlier than that in the western world.